Assessment of health and trauma by vehicular collisions in wild mammals from three biomes in Brazil: anthropogenic impacts on Brazilian biodiversity - Suarez, Pedro Enrique Navas (2022)
Direct mortality from motor vehicle collisions (MVC) is one of the greatest road- related threats to wildlife. In Brazil, the estimated annual wildlife mortality on the road ranges from 14 to 475 million individuals. Furthermore, the World Bank estimates that at least 25 million kilometers of new roads will be built in the next 30 years, mainly in developing countries in tropical regions. Thus, road mortality is expected to be a serious threat to biodiversity if planned and built roads do not implement an environmental program (e.g., fences, underpasses, overpasses). Simultaneously, considering that some health aspects of Neotropical biodiversity still need to be elucidated, MVC is presented as an excellent opportunistic source of data/samples. In this context, this doctoral thesis aimed to expand the knowledge about the MVC- traumatic injuries (MVC-TI) in wild mammals collected in three Brazilian biomes; in addition, as a contribution to the health data of neotropical wild mammals, pathological, molecular, parasitological, and toxicological studies were carried out. Chapter 1 presents a literature review, which seeks to contextualize road development in Brazil from political, economic, and environmental perspectives. Chapter 2 presents a detailed description of the topographical patterns of MVC-TI in the different species of wild mammals studied. Finally, chapter 3 and appendix detail health aspects. The literature review suggests that political and economic interests were important for the Brazilian government to opt for road development over other transport modes, such as railroads and waterways. Although Brazil has one of the most extensive road networks globally, the lack of budget makes it challenging to maintain the network, which explains some roads\' low quality and minimal environmental suitability. Furthermore, environmental legislation is relatively new, beginning in the 1980s. Some highways (toll and federal/state) currently recognize their environmental impacts and have implemented mitigation and compensation programs. However, there are still road projects that can be harmful to biodiversity. Subsequently, the biomechanical compression of MVC-TI helps understand the distribution and severity of these injuries. So, this author considers that the description and frequency of the lesions observed for each taxon studied can help veterinarians who perform emergency care for specimens that remain alive after MVC. Finally, among the main results on health aspects, it is highlighted the description of pulmonary adiaspiromycosis, a neglected zoonotic fungal disease in two armadillo species, and a toxicology study detecting three currently banned pesticides in some wild carnivore species. This author confidently believes that the results presented here can be of great importance to make society aware of the negative impacts of roads on fauna; likewise, from a one health perspective, the use of these specimens in national or state health surveillance programs seems to be a remarkable strategy.